Leukemia Inhibitory Factor Facilitates Self-Renewal and Differentiation and Attenuates Oxidative Stress of BMSCs by Activating PI3K/AKT Signaling. (5th September 2022) - Liang, Youde; Zhou, Ruiping; Liu, Xin; You, Lin; Chen, Chang; Ye, Xiaoling; Wei, Wei; Liu, Jie; Dai, Jiawei; Li, Kaixiong; Zhao, Xiangxiang
Abstract : Objective . Transplantation of bone marrow-derived mesenchymal stem cells (BMSCs) remains a hopeful therapeutic approach for bone defect reconstruction. Herein, we investigated the effects and mechanisms of leukemia inhibitory factor (LIF) in the function and viability of hypoxic BMSCs as well as bone defect repair. Methods . The effects of LIF on apoptosis (flow cytometry, TUNEL staining), mitochondrial activity (JC-1 staining), proliferation (colony formation, EdU staining), and differentiation (CD105, CD90, and CD29 via flow sorting) were examined in hypoxic BMSCs. LIF, LIFR, gp130, Keap1, Nrf2, antioxidant enzymes (SOD1, catalase, GPx-3), bone-specific matrix proteins (ALP, BSP, OCN), PI3K, and Akt were detected via immunoblotting or immunofluorescent staining. BMSCs combined with biphasic calcium phosphate scaffolds were implanted into calvarial bone defect mice, and the therapeutic effect of LIF on bone defect was investigated. Results . Hypoxic BMSCs had increased apoptosis and oxidative stress and reduced mitochondrial activity. Additionally, LIF, LIFR, and gp130 were upregulated and PI3K/Akt activity was depressed in hypoxic BMSCs. Upregulated LIF alleviated apoptosis and oxidative stress and heightened mitochondrial activity and PI3K/Akt signaling in hypoxic BMSCs. Additionally, LIF overexpression promoted self-renewal and osteogenic differentiation of BMSCs with hypoxic condition. Mechanically, LIF facilitated self-renewal and differentiation as well as attenuated oxidative stress of BMSCs through enhancing PI3K/AKT signaling activity. Implantation of LIF-overexpressed BMSC-loaded BCP scaffolds promoted osteogenesis as well as alleviated oxidative stress and apoptosis through PI3K/Akt signaling. Conclusion . Our findings demonstrate that LIF facilitates self-renewal and differentiation and attenuates oxidative stress of BMSCs by PI3K/AKT signaling.